Recommendations regarding Neurospora genetic nomenclature - D. D. Perkins (Fungal Genetics Reports, 1996)
Proposals are made that concern (1) distinguishing (in gene symbols) between locus numbers and numbers that describe a product or phenotype, (2) numbering of gene loci, (3) priority of gene names and symbols, and (4) symbolism for heterokaryons.